Studies on patristic texts and archaeology: if these stones could speak...; essays in honor of Dennis Edward Groh - Kalantzis, George; Groh, Dennis; Martin, Thomas F. (Hors série, 2009)
Introduction / George Kalantzis & Thomas F. Martin -- A surprise for simplician / J. Patout Burns -- Holy impudence, sacred desire : the women of Matthew 1:1-16 in Syriac tradition / Susan Ashbrook Harvey -- Between two thieves : Novatian of Rome and kenosis Christology / James L. Papandrea -- Counting the years from the destruction of the Temple : Jewish piety and polemics in late antique Palestine / Jason Moralee -- Baptism ad sanctos? / Robin M. Jensen -- A pagan and Christian 5th-6th century bread mould? An artifact reconsidered / Robert C. Gregg -- Archaeology and religion / James F. Strange -- Women's and children's costumes : indications of social status in the Piazza Armerina mosaics / Lucille A. Roussin -- A silver amulet from Sepphoris, Israel / C. Thomas McCollough & Beth Glazier-McDonald -- These stones can speak / Thomas R.W. Longstaff